Ruthenium-catalyzed C–H activation of thioxanthones - Wagner, Danny; Bräse, Stefan (Beilstein Journal of Organic Chemistry, 2015)
Thioxanthones – being readily available in one step from thiosalicylic acid and arenes – were used in ruthenium-catalyzed C–H-activation reaction to produce 1-mono- or 1,8-disubstituted thioxanthones in good to excellent yields. Scope and limitation of this reaction are presented.
Keywords: C–H activation; metal catalysis; thioxanthones